Síntese de um derivado trioxigenado a partir da carvona visando a preparação de a-metileno-y-butirolactonas monoterpênicas - César, Roberta Cecília Vettoraci (2015)
The lactone function is present in a large number of natural compounds that presents biological activities. Within the lactone functionality, the a-methylene-?-butyrolactone and the y-butyrolactone have already known diverse biological activities. In this paper was used the (R)-(-) carvone as the start material, a variety of methodologies was tested to develop and create a methodological sequence of carbon atoms oxygenation to produce a new synthon to build butyrolactone derivatives. The synthetic route developed applies classic functional transformations of relative simplicity, such as reduction reactions, oxidation, and functional group protections, among others. In general the reactions were of simple execution and the outcomes were significant, however the purification processes were not always sufficient. Among the reaction processes the methodology adaptation of the hydroxyl of the epoxy alcohol (64) protection stands out, looking for the preparation of the benzyloxy (65), that has been extremely important to improve the outcome of this reaction step. Besides the acetate group of the compound (64) hydrolysis was a surprise, one that helped reduce a step in the previous planned reaction sequence. Thus the planned synthetic route enabled the oxygenated intermediate (67) with 28,5% of outcome that will serve as a new synthon. Yet it will be possible to see a real possibility of application of the route developed in this work to prepare more complex synthons looking for the construction of monoterpeness ?-methyl-y-butyrolactone and the ybutyrolactone derivates.